1999
DOI: 10.1037/0022-006x.67.3.362
|View full text |Cite
|
Sign up to set email alerts
|

The socioeconomic impact of interpersonal violence on women.

Abstract: Prospective data from a nationally representative sample of women were used to examine 4 objective indexes of social adjustment following direct, interpersonal crime. Household income, marital status, employment, and education level were evaluated as risk factors for and outcomes of victimization. Data were collected in 3 waves at 1-year intervals, and 2,863 women completed all 3 waves. Results indicate that women experience increased risk for victimization when income is below poverty level and when newly div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
88
2
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(99 citation statements)
references
References 19 publications
6
88
2
1
Order By: Relevance
“…Battered teenage mothers on welfare who reported higher levels of depression also reported greater levels of economic strain (Kalil & Danziger, 2000). These findings are consistent with other reports that women who are victims of violence are at risk of subsequent disruption in resources such as employment and reduced income following victimization, suggesting that psychological distress may be an underlying mechanism for resource loss in victims of violence (Byrne, Resnick, Kilpatrick, Best, & Saunders, 1999;Monnier, Resnick, Kilpatrick, & Seals, 2002). To date, no studies have investigated the potential mediating effect of psychological distress on economic outcomes among women experiencing intimate partner violence.…”
Section: Effects Of Psychological Distress On the Economic Outcomes Osupporting
confidence: 86%
“…Battered teenage mothers on welfare who reported higher levels of depression also reported greater levels of economic strain (Kalil & Danziger, 2000). These findings are consistent with other reports that women who are victims of violence are at risk of subsequent disruption in resources such as employment and reduced income following victimization, suggesting that psychological distress may be an underlying mechanism for resource loss in victims of violence (Byrne, Resnick, Kilpatrick, Best, & Saunders, 1999;Monnier, Resnick, Kilpatrick, & Seals, 2002). To date, no studies have investigated the potential mediating effect of psychological distress on economic outcomes among women experiencing intimate partner violence.…”
Section: Effects Of Psychological Distress On the Economic Outcomes Osupporting
confidence: 86%
“…Recent research have also indicated that physical assault in adulthood, is a risk factor of women's poverty and makes the victims economically dependent on their partners [31,32,34]. Poverty as a source of daily stress also results in emotional arousal and dysregulation which in turn makes the victims unable to function and causes anxiety [22].…”
Section: Risk Factorsmentioning
confidence: 99%
“…A study of 331 discharged psychiatric inpatients (male and female) found that being an urban resident, using alcohol or drugs, and experiencing transient living conditions before hospitalization were associated with violent victimization (Hiday et al 2002a). Overall, research has shown that being divorced or unmarried, unemployment, ethnic minority status, poverty, homelessness and substance abuse are associated with interpersonal assault in adulthood (Amaya-Jackson et al 1999;Bassuk et al 1998;Byrne et al 1999;Switzer et al 1999). …”
Section: Introductionmentioning
confidence: 99%